2008
DOI: 10.1007/978-3-540-89224-3
|View full text |Cite
|
Sign up to set email alerts
|

Metrics for Process Models

Abstract: PrefaceBusiness process modeling plays an important role in the management of business processes. As valuable design artifacts, business process models are subject to quality considerations. The absence of formal errors such as deadlocks is of paramount importance for the subsequent implementation of the process. This book develops a framework for the detection of formal errors in business process models and for the prediction of error probability based on quality attributes of these models (metrics). We focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(19 citation statements)
references
References 195 publications
0
18
0
1
Order By: Relevance
“…In particular, it is possible to measure the quality of such model through a set of metrics. The use of metrics to evaluate the quality of process models has been thoroughly investigated in the literature [11][12][13][14], but here we focus on a set of metrics that are more tailored to the hierarchical model that is at the core of our approach. Specifically, such hierarchical model should be "balanced" in the sense that all of its components -i.e.…”
Section: Approach Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, it is possible to measure the quality of such model through a set of metrics. The use of metrics to evaluate the quality of process models has been thoroughly investigated in the literature [11][12][13][14], but here we focus on a set of metrics that are more tailored to the hierarchical model that is at the core of our approach. Specifically, such hierarchical model should be "balanced" in the sense that all of its components -i.e.…”
Section: Approach Overviewmentioning
confidence: 99%
“…In the literature, there are several metrics that have been proposed for the analysis of business process models [11][12][13][14]. In some cases, these metrics have their origin in network analysis and software engineering.…”
Section: Evaluation Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that the graphical portrayal of these types of features provides additional support for understanding, implementing, executing, measuring, analysing, improving, and controlling business processes. According to Mendling, business process models can be considered to be the conceptual artefacts underpinning the management of organisational processes [1]. In turn, BPM has evolved into a valuable approach to defining and documenting business processes [2], which are considered an important prerequisite for organisations that intend to engage in business process improvement and management initiatives [3].…”
Section: Introductionmentioning
confidence: 99%